2007
DOI: 10.1103/physrevlett.98.251302
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Magnetic Fields in Freely Decaying Magnetohydrodynamic Turbulence

Abstract: We study the evolution of magnetic fields in freely decaying magnetohydrodynamic turbulence. By quasi-linearizing the Navier-Stokes equation, we solve analytically the induction equation in quasinormal approximation. We find that, if the magnetic field is not helical, the magnetic energy and correlation length evolve in time respectively as EB ∝ t −2(1+p)/(3+p) and ξB ∝ t 2/(3+p) , where p is the index of initial power-law spectrum. In the helical case, the magnetic helicity is an almost conserved quantity and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 12 publications
5
103
3
Order By: Relevance
“…[11], it was shown that Eqs. (10)- (12) remain invariant in the expanding Universe when time derivatives @=@t are replaced by scale factor derivatives ðH 0 =aÞ@=@ ln a, and physical quantities in the integrands of Eqs. (10)-(12) are replaced by their comoving analogues.…”
Section: Time Evolution Of the Magnetic And Kinetic Energy Contenmentioning
confidence: 99%
See 1 more Smart Citation
“…[11], it was shown that Eqs. (10)- (12) remain invariant in the expanding Universe when time derivatives @=@t are replaced by scale factor derivatives ðH 0 =aÞ@=@ ln a, and physical quantities in the integrands of Eqs. (10)-(12) are replaced by their comoving analogues.…”
Section: Time Evolution Of the Magnetic And Kinetic Energy Contenmentioning
confidence: 99%
“…Equations (10)- (12) are a set of well-defined equations, since they ensure conservation of energy, momentum, mass, and helicity density to the lowest nontrivial order in Át.…”
Section: Time Evolution Of the Magnetic And Kinetic Energy Contenmentioning
confidence: 99%
“…when K d = 0. time evolution of the magnetic field is owing to the MHD turbulence effects accounted for in Eqs. (5)- (8) and (14)- (17). Let us define the scale of the magnetic field as Λ = 1/k.…”
Section: Numerical Solution Of the Evolution Equationsmentioning
confidence: 99%
“…The MHD turbulence was found in Ref. [17] to take place when both the Reynolds number, Re = vl/ν, and the magnetic Reynolds number, Re B = vlσ cond , are large. Here v and l are the typical velocity and length scales of the matter motion, ν is the kinematic viscosity, and σ cond is the quark matter conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the inverse cascade mechanism, λ(t) grows faster than a(t) due to the turbulence in the plasma [54]. In this case, the magnetic helicity is approximately conserved but the energy is transferred from small scales to large scales [71], and the spectrum develops with a characteristic scaling law [72]. After recombination, the plasma becomes neutral and the magnetic fields evolve trivially.…”
Section: Summary and Discussionmentioning
confidence: 99%